Propuesta de manejo pesquero en la cuenca media del río Nanay (reserva nacional Allpahuayo Mishana) en el período 2011 - 2014 - Díaz Alva, Johny (2016)
The purpose of this professional services report was to know the fisheries management activities in the middle basin of the Nanay River (Allpahuayo Mishana National Reserve) in the period 2011 - 2014. The data collection was carried out by applying the participatory and active methodology among the inhabitants and State entities. In addition, the information collected in the workshops (referring to the fishing extraction ponds) was verified through direct observation during the tours that were carried out as part of the surveillance and control. The environmental characteristics of the middle basin of the Nanay River were carried out through specialized bibliographic review. The data were processed in the Excel program to determine the catch quotas and decision-making for a sustainable use of the resource. The specific richness of fish in the middle basin of the Nanay River was 106 species between fish for human consumption and ornamental. Of the 24 recognized fish families, those that report the greatest diversity are Pimelodidae (17 species), Cichlidae (13 species), Characidae (9 species), Anostomidae and Serrasalmidae (each with 6 species) and the others with a lower number of species . For fishing management, 17 ornamental species and 13 species for human consumption were selected, managed by 07 Associations of Artisanal Fishermen from 08 communities. The use is included between the months of: January to May of all years, for "black band" and "curuhuara" and, between the months of June to October for the rest of ornamental fish and for human consumption. It has been possible to determine the catch quotas of 17 ornamental species and 13 of human consumption that to date have been giving adequate results to achieve a sustainable use of the species.